2016
DOI: 10.1016/j.jaci.2015.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Filaggrin-null mutations are associated with increased maturation markers on Langerhans cells

Abstract: BackgroundMutations in the gene encoding filaggrin (FLG), an epidermal structural protein, are the strongest risk factor identified for the development of atopic dermatitis (AD). Up to 50% of patients with moderate-to-severe AD in European populations have FLG-null alleles compared with a general population frequency of 7% to 10%.ObjectiveThis study aimed to investigate the relationship between FLG-null mutations and epidermal antigen-presenting cell (APC) maturation in subjects with and without AD. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
27
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 36 publications
3
27
1
1
Order By: Relevance
“…Both CD86 and OX40L were significantly upregulated in UVB‐irradiated skin compared with nonirradiated skin (both P < 0·001; n = 16). A recent study suggested that FLG heterozygous patients may have increased LC maturation due to lower epidermal levels of cis ‐urocanic acid . However, we found no difference between FLG wild‐type and heterozygous patients in UVB‐induced upregulation of CD86 and OX40L.…”
contrasting
confidence: 86%
“…Both CD86 and OX40L were significantly upregulated in UVB‐irradiated skin compared with nonirradiated skin (both P < 0·001; n = 16). A recent study suggested that FLG heterozygous patients may have increased LC maturation due to lower epidermal levels of cis ‐urocanic acid . However, we found no difference between FLG wild‐type and heterozygous patients in UVB‐induced upregulation of CD86 and OX40L.…”
contrasting
confidence: 86%
“…In accordance with these mouse studies, LCs in the lesional skin of AD reportedly exhibit an activated phenotype, and TSLP is highly expressed in AD lesions . Moreover, mutations in the FLG gene may influence the activation of LCs not only in AD patients but also non‐AD healthy controls . These results suggest that LCs also induce Th2‐type immune responses in human AD.…”
Section: The Roles Of Cutaneous Dcs In Adsupporting
confidence: 73%
“…11 Moreover, mutations in the FLG gene may influence the activation of LCs not only in AD patients but also non-AD healthy controls. 93 These results suggest that LCs also induce Th2-type immune responses in human AD.…”
Section: Cutaneous Dcs In the Pathogenesis Of Admentioning
confidence: 83%
“…FLG null mutations also heightened the immune imbalance between Th-1e, Th-2e, and Th-17elike Tregs in AD. 88 Leitch et al 89 showed that FLG null mutation carriers have more mature Langerhans cells in nonlesional skin irrespective of whether they have a diagnosis of AD. Also, filaggrin degradation products, including the cis-isomer of urocanic acid, were shown to down-regulate the expression of dendritic cells and increase the production of regulatory T-cells.…”
Section: Filaggrin Interactions With Dysregulated Immune Responses Inmentioning
confidence: 99%
“…Also, filaggrin degradation products, including the cis-isomer of urocanic acid, were shown to down-regulate the expression of dendritic cells and increase the production of regulatory T-cells. 89 Filaggrin-deficient mice were shown to have higher levels of peripheral Th17 cells than their wild-type controls. This observation was present in adult ft/ft mice but not in 2-week-old ft/ft mice, indicating that this must be an acquired phenomenon.…”
Section: Filaggrin Interactions With Dysregulated Immune Responses Inmentioning
confidence: 99%